Probing Arts and Emergent Forms of Life - Fischer, Michael M. J., 1946- (Book collections on Project MUSE., 2023)
"In Probing Arts and Emergent Forms of Life Michael M. J. Fischer calls for a new anthropology of the arts that attends to the materialities and technologies of the world as it exists today. Fischer examines the work of key Southeast and East Asian artists within the crucibles of unequal access, geopolitics, the reverberations of past traumas, and emergent new socialities. He outlines how artist-theorists including Entang Wiharso, Sally Smart, Charles Lim, Zai Kuning, and Kiran Kumar speculate on how the world is changing in ways that are attuned to cultivating, repairing, and rethinking the world in the Anthropocene. Their artistic vocabulary not only undoes Western art models and categories; it probes the unfolding future, addresses past trauma, and creates contested, vibrant, and flourishing spaces. Throughout Indonesia, Korea, Singapore, Thailand, and Vietnam, and from Kumar's experimental dance to Kuning's rattan and beeswax ghost ships to Lim's videography of Singapore from the sea, Fischer argues that these artists' theoretical discourses should be privileged over those of the curators, historians, critics, and other gatekeepers who protect and claim art worlds for themselves"--